The Psychological Conflicts of the Main and Secondary Characters of The Lady With The Dog - Ni Made Ayu Sintya Paramita Dewi; I Nengah Sudipa; A.A. Sg. Shanti Sari Dewi; Ni Made Ayu Widiastuti (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study entitled The Psychological Conflicts of the Main and Secondary Characters of the "The Lady with the Dog". The study aims at identifying, classifying, and analyzing the conflict, psychological conflict, and motivation of the main and secondary characters in the story. This study is done by qualitative method; the data were collected from the short story Lady with The Dog in the form of passages or utterances that express the characters' conflict. The short story tells about the affair between Dmitrich Gurov, the main character, and Anna Sergeyvna, the secondary character. The data were collected by documentation and note-taking technique. After being collected, the data were analyzed with three theories: the theory of conflict by William Kenney, the psychoanalytic theory by Freud cited from Nayar, and the theory of human motivation proposed by Maslow. The findings reveal that the main and secondary characters face internal and external conflicts. Their external conflicts were caused by their unwell relationship with their suppose; meanwhile, their internal conflicts were caused by their inability to control their tripartite psyche. Their decision to have an affair also occur due to some motivation based on their unsatisfied love needs.